Productivity of Oil Palm Plants (Elaeis Guineensis Jacq) on Mineral Land Conversion from Rubber Plants in Tamora Plantation PT. Perkebunan Nusantara V - Prastikha, Dikha (Journal of Engineering Science and Technology Management, 2024)
The company converted rubber plantations into palm oil plantations to enhance operational efficiency. Palm oil is considered more profitable as its maintenance is simpler, production costs are lower, and harvesting can be done year-round without being affected by the seasons, unlike rubber, whose production decreases significantly during the rainy season. This is expected to increase the company's overall productivity and profitability. This research aims to determine the productivity of palm oil and the soil nutrients in the rubber-converted land at Kebun Tamora, PT. Perkebunan Nusantara V, Kampar Regency, Riau. The research was conducted from September 1 to November 1, 2023, using a quantitative and qualitative descriptive analysis method, utilizing secondary data. The results indicate that plantation productivity varies but has shown continuous increases year after year. For example, for the 2014 planting year, production increased from 16.150 tons/ha in 2018 to 33.127 tons/ha in 2022, while for the 2015 planting year, productivity reached 31.867 tons/ha in 2022.